Liver Fibrosis Indices and Outcomes After Primary Intracerebral Hemorrhage. Issue 3 (March 2020) - Parikh, Neal S.; Kamel, Hooman; Navi, Babak B.; Iadecola, Costantino; Merkler, Alexander E.; Jesudian, Arun; Dawson, Jesse; Falcone, Guido J.; Sheth, Kevin N.; Roh, David J.; Elkind, Mitchell S.V.; Hanley, Daniel F.; et al.
Abstract : Background and Purpose—: Cirrhosis—clinically overt, advanced liver disease—is associated with an increased risk of hemorrhagic stroke and poor stroke outcomes. We sought to investigate whether subclinical liver disease, specifically liver fibrosis, is associated with clinical and radiological outcomes in patients with primary intracerebral hemorrhage. Methods—: We performed a retrospective cohort study using data from the Virtual International Stroke Trials Archive–Intracerebral Hemorrhage. We included adult patients with primary intracerebral hemorrhage presenting within 6 hours of symptom onset. We calculated 3 validated fibrosis indices—Aspartate Aminotransferase–Platelet Ratio Index, Fibrosis-4 score, and Nonalcoholic Fatty Liver Disease Fibrosis Score—and modeled them as continuous exposure variables. Primary outcomes were admission hematoma volume and hematoma expansion. Secondary outcomes were mortality, and the composite of major disability or death, at 90 days. We used linear and logistic regression models adjusted for previously established risk factors. Results—: Among 432 patients with intracerebral hemorrhage, the mean Aspartate Aminotransferase–Platelet Ratio Index, Fibrosis-4, and Nonalcoholic Fatty Liver Disease Fibrosis Score values on admission reflected intermediate probabilities of fibrosis, whereas standard hepatic assays and coagulation parameters were largely normal. After adjusting for potential confounders, Aspartate Aminotransferase–Platelet Ratio Index was associated with hematoma volume (β, 0.20 [95% CI, 0.04–0.36]), hematoma expansion (odds ratio, 1.6 [95% CI, 1.1–2.3]), and mortality (odds ratio, 1.8 [95% CI, 1.1–2.7]). Fibrosis-4 was also associated with hematoma volume (β, 0.27 [95% CI, 0.07–0.47]), hematoma expansion (odds ratio, 1.9 [95% CI, 1.2–3.0]), and mortality (odds ratio, 2.0 [95% CI, 1.1–3.6]). Nonalcoholic Fatty Liver Disease Fibrosis Score was not associated with any outcome. Indices were not associated with the composite of major disability or death. Conclusions—: In patients with largely normal liver chemistries, 2 liver fibrosis indices were associated with admission hematoma volume, hematoma expansion, and mortality after intracerebral hemorrhage. Abstract : Supplemental Digital Content is available in the text.